Impact of Family Background and Individual Characteristics on Vocational High School Choice in South Korea: A Gender Analysis - Choi, Seonkyung (Journal of Technical Education and Training, 2020)
At the end of compulsory school, adolescents in many industrialised countries must make an important and far-reaching decision that strongly influences their future working life. Few of the many studies of school choice in South Korea have empirically analysed the choice of type of upper secondary school and almost none have paid attention family background and individual characteristics. This paper does so for both boys and girls completing compulsory lower secondary education, using 11 years’ data from the Korea Education and Employment Panel (KEEP) of the Korea Research Institute for Vocational Education and Training from a period before recent Korean vocational educational policy changes. We use a Probit model to deal with binary variables. Key variables considered include teacher assessments of students, father’s income, father’s education, spending on private tutoring at the lower secondary level, and the number of siblings, these last two never previously analyzed. In addition, to gender analysis this paper confirms previous results that parental social status is a major determinant of high school choice between general and vocational education. The key gender result is that fathers’ educational attainment negatively and significantly affects females more than males, and that fathers’ high income more negatively and significantly affects males than females in nonattendance at vocational high school. This paper also confirms previous findings that females were more motivated than males to enroll in vocational high school. Vocational education better meets females’ needs than males’, especially those not well supported by their parents. These findings imply that future research on both Korea and other countries needs to pay much more attention to family and individual characteristics and to differences between genders.